2020
DOI: 10.3389/fpsyg.2020.567155
|View full text |Cite
|
Sign up to set email alerts
|

Motherhood in the Time of Coronavirus: The Impact of the Pandemic Emergency on Expectant and Postpartum Women’s Psychological Well-Being

Abstract: The birth of a child is a critical and potentially stressful experience for women, entailing several changes both at the individual and interpersonal level. This event can lead to different forms of distress, ranging in intensity and duration. Many studies highlighted medical, psychological, and social variables as risk factors potentially influencing the onset or aggravation of perinatal maternal conditions. The current pandemic emergency and the restrictive measures adopted by local governments to prevent th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
111
1
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 107 publications
(120 citation statements)
references
References 87 publications
5
111
1
3
Order By: Relevance
“…During the pandemic's first wave, women with confirmed SARS-CoV-2 infection, suspected cases, and sometimes even women not affected by the virus too often gave birth alone in the name of "safety" and were separated from their babies in the name of "precaution". Instead, some Italian studies have successively suggested that the lack of presence of one's partner during labour and delivery might predict its impact on postpartum women's mental health well-being [5,20]. Even though definitive evidence showing that early separation improves neonatal outcomes is still lacking, the short-and long-term benefits of bonding and breastfeeding are universally recognised [2,3].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…During the pandemic's first wave, women with confirmed SARS-CoV-2 infection, suspected cases, and sometimes even women not affected by the virus too often gave birth alone in the name of "safety" and were separated from their babies in the name of "precaution". Instead, some Italian studies have successively suggested that the lack of presence of one's partner during labour and delivery might predict its impact on postpartum women's mental health well-being [5,20]. Even though definitive evidence showing that early separation improves neonatal outcomes is still lacking, the short-and long-term benefits of bonding and breastfeeding are universally recognised [2,3].…”
Section: Discussionmentioning
confidence: 99%
“…Skin-to-skin contact, rooming-in, and breastfeeding were all recommended practices unless the mother was acutely ill as the benefits outweigh the potential risks of SARS-CoV-2 transmission and subsequent development of COVID-19 [1][2][3][4]. Mother and baby separation was not advised, and the lack of presence of one's partner during labour and delivery was found to predict postpartum women's mental health in some studies conducted in Italy [5]. Currently, however, protecting childbirth physiology and preserving the mother-child bond during the COVID-19 pandemic is still a global challenge.…”
Section: Introductionmentioning
confidence: 99%
“…Postpartum women are at greater vulnerability to mental health issues compared with other women related to transition to motherhood 2 . Concerns about the pandemic and public health measures to curb the spread, such as quarantine and limited access to friends, family and health professionals could contribute to the worsened psychological wellbeing now reported in pregnant and postpartum mothers during this pandemic 3 . In semi-structured interviews that we conducted with postpartum women, women described their experience of being in lockdown as 'stuck in a little house with not enough space', 'less optimistic' and 'losing clarity of thought', which supports the findings of Ceulemans et al (2021) 1 .…”
Section: Mental Health Among Postpartum Women During the Covid-19 Panmentioning
confidence: 99%
“…In a national cross-sectional survey conducted in Italy, Ravaldi et al [15] reported signi cant changes in pregnant women's expectations regarding childbirth where they expressed more fear, anxiety, pain and loneliness during this current pandemic. They also found that women with a history of psychological distress were signi cantly more likely to be overwhelmed by the situations caused by the COVID-19 pandemic [15,16]. Another study on COVID-19 awareness among pregnant women revealed that social demographic factors such as maternal age, ethnicity, frontline jobs and attendance at high-risk clinics are likely to in uence the attitudes and precaution practices among of pregnant women [17].…”
Section: Discussionmentioning
confidence: 99%